Review and analysis of telework perspective in the administrative systems - Hamed Kord; Yousef Noushiravani; Mohammad Davoud Bahadori; Mosayeb Jahantigh (Dutch Journal of Finance and Management, 2017)
Current world is full of change and transformation. In the corporate world, these changes are more intense and intelligent measures to respond to these changes are inevitable. Basis of majority of the organizational change is growth and impressive technology, communications and information technology. In the present era the information technology directly affects all levels of the human individual and social life is broad and deep. One of the areas of change is how people work in organizations. Severe changes in crowd composition of the workforce and the increasing entry of women into organizations that contribute to the balance between work and family life, in addition to damages such as air pollution, high consumption of fuel and energy, traffic etc. led to a growing interest organizations and communities, has been created a phenomenon called of "telework". In this paper we try to present a theoretical framework, studied the process of expanding, requirements and challenge of teleworking phenomenon and suggestion the executive solutions for its correct application in the organization.
Keywords: 650; organization; information technology; telework